Enlightenment-mysticism poetry-as a means of upbringing (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides reflections on the illumination of enlightened and mystical ideas in current Uzbek poetry. Through the analysis of the poems of Asqar Mahkam and Abduvali Qutbiddin, the reflection of the mysticism tradition in modern poetry, the skill of the creator, is poet logically drawn into analysis. Enlightenment-mysticism as a medium of upbringing is becoming one of the leading themes of modern poetry, and this article gives a detailed idea of it.